2018
DOI: 10.1094/phyto-12-16-0431-r
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Marker-Based Genomic Estimated Breeding Values and Phenotypic Evaluation for Selection of Bacterial Spot Resistance in Tomato

Abstract: Bacterial spot affects tomato crops (Solanum lycopersicum) grown under humid conditions. Major genes and quantitative trait loci (QTL) for resistance have been described, and multiple loci from diverse sources need to be combined to improve disease control. We investigated genomic selection (GS) prediction models for resistance to Xanthomonas euvesicatoria and experimentally evaluated the accuracy of these models. The training population consisted of 109 families combining resistance from four sources and dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 47 publications
0
38
0
Order By: Relevance
“…RR-BLUP successfully recognized complex patterns with additive effects and delivered good GP in wheat disease resistance [50]. Furthermore, RR-BLUP has a clearcut computational efficiency [11,49,51,52]. In this study, GP accuracy does not vary in three different models ( Figure S1) and the RR-BLUP model with the 500 QTL markers and the 5-year mean PS produced high prediction accuracy and is therefore recommended for the prediction of PR in flax.…”
Section: Accuracy Of Gp Modeling By Environment Training Populationmentioning
confidence: 65%
See 1 more Smart Citation
“…RR-BLUP successfully recognized complex patterns with additive effects and delivered good GP in wheat disease resistance [50]. Furthermore, RR-BLUP has a clearcut computational efficiency [11,49,51,52]. In this study, GP accuracy does not vary in three different models ( Figure S1) and the RR-BLUP model with the 500 QTL markers and the 5-year mean PS produced high prediction accuracy and is therefore recommended for the prediction of PR in flax.…”
Section: Accuracy Of Gp Modeling By Environment Training Populationmentioning
confidence: 65%
“…Therefore, diverse phenotypic and genetic variabilities within the flax core collection render it useful as a resource for breeding and as a TP for GP model construction. [11,14,42,[47][48][49]. For example, comparisons among RR-BLUP, Bayes-Cπ, and RKHSR showed no difference in accuracies in a wheat FHB study [19].…”
Section: Accuracy Of Gp Modeling By Environment Training Populationmentioning
confidence: 98%
“…Genomic selection (GS), which uses genome-wide markers to predict breeding values, may greatly improve the selection gain in breeding programs for complex traits controlled by several minor genes. In last year, pioneer studies concerning the application of GS to transfer yield-related traits in tomato varieties from wild related species were reported [ 22 , 23 ] as well as to assess the potential of GS to increase soluble solids content and fruit weight in F1 tomato varieties [ 24 ] and to develop bacterial spot resistant tomato lines [ 25 ]. GS models were widely exploited for predicting phenotypes of progeny and parents, although the efficiency varied depending on the parental cross combinations and the selected traits [ 26 ].…”
Section: The Tomato Genetic Backgroundmentioning
confidence: 99%
“…The effectiveness of GEBVs for prediction was mainly demonstrated in polyploid wheat [ 27 , 52 , 53 , 54 , 55 , 56 , 57 ] but studies are also available for diploids rice [ 54 , 58 ], barley [ 59 , 63 ], soybean [ 60 , 61 ], maize [ 27 , 62 ] and tomato [ 22 , 23 , 24 , 25 ]. Lorenzana and Bernardo [ 59 ] obtained GEBV accuracies between 0.64 and 0.83 using 150 DHs (doubled-haploid) barley lines and 223 Restriction Fragment Length Polymorphism (RFLP) markers to improve grain yield and amylase activity.…”
Section: Lesson From Other Speciesmentioning
confidence: 99%
“…Duangjit et al [67] studied the potential of GS in tomato breeding programs to improve fruit quality traits in tomato. In the case of BS disease resistance, Liabeuf et al, [68] observed higher prediction accuracy through the GS model for resistance to X. euvesicatoria compared to phenotypic selection.…”
Section: Genomics-assisted Breeding Approaches (Gba)mentioning
confidence: 99%